Modelagem 3-D de estruturas geológicas complexas - NASCIMENTO, Elias Pereira (2019)
In areas of the subsurface the presence of complex geological structures (e.g. faults, recumbent folds, dikes, diabase sills, salt domes, etc) reduces the seismic imaging quality due to false structures. This difficult the success of finding oil and recovering greater amount from existing wells. New technologies (e.g. modeling and visualization) are being more and more used as a tool to increase the ability to find new hydrocarbon reserves and improves the efficiency of oil and gas exploration. With the seismic surveys and geophysical studies complete, geologists build a digital 3-D geomodel of the subsurface to help decide whether to develop an oil or gas field. Geomodeling is a vital riskminimizing tool. In the oil and gas industry 3-D earth models are crucial decision making and other purposes: to check the consistency between geological objects, to plan the path of non-vertical wells, to monitor the reservoir (4-D seismic), for the reservoir model construction, seismic inversion and velocity analysis. In this work was used the 3-D modeling as tool to modeling complex geological structures. The models correspond to complex and synthetic 3-D models. The types of models were: structural, stratigraphic and velocity. Additionally images had been generated to visualize the structure internal of the studied geological structures. That is very important for the study of the petrophysical properties and the fluid flow in the interior of one determined reservoir.